Penyederhanaan Kaidah Nahwu dengan Buku Al-Fahmu - Syaepullah, Syaepullah (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2025)
Many people believe that learning Arabic is difficult due to the numerous branches of knowledge within it, one of which is Nahwu (Arabic grammar). This subject is often taught using Arabic-language books such as Al-Ajurrumiyyah and Al-Nahwu Al-Wadhih, with a learning method that emphasizes memorization. As a result, achieving a deep understanding requires two stages: the first is understanding the vocabulary of the material, and the second is grasping the meaning of the material itself. This process leads to an extended duration for learning Nahwu.This paper aims to simplify the rules and material to make them easier to understand by using a qualitative research method, focusing on students who have studied Al-Ajurrumiyyah and Al-Nahwu Al-Wadhih. The research involves interviews, observations, and documentation, with the theory presented through comparisons and logic, without relying on memorization.’The research results show that the Al-Fahmu method is easier to learn than the previous books studied because it uses the Indonesian language, simplifies the rules, and provides examples with easy but varied vocabulary.